Supermarket market-channel participation and technology decisions of horticultural producers in Brazil - Mainville,Denise Y. (2007)
This paper examined the relationships between growers choice of market channel (emphasizing the supermarket market-channel versus others), technology use, and grower characteristics such as human capital and farm size. Three key findings emerged. First, both tomato and lettuce growers selling to the supermarket market-channel had more human capital than those not participating. Second, while farm size was important in whether lettuce growers sell to supermarkets, it was not important for tomato growers. Third, technology use was significantly more capital-intensive among lettuce growers selling to the supermarket channels, however, that was generally not the case for tomato growers. These results are important to agribusiness researchers and policymakers interested in technology design and research and extension to enable producers to adapt to the needs of changing agrifood markets, with new requirements of attributes of products and transactions, which in turn have implications for technology adoption and human capital investment among growers. This is particularly pressing in places like Brazil where the market for horticultural products is changing quickly, conditioned by the rapid rise of supermarkets.